(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2014)
In this work, we were interested to the interactions of various light gases (critical temperature not exceeding 31 Â°C) with the zeolite ZK-4 and its varieties exchanged at temperatures close to ambient. The interest first practice since these gases are frequently encountered in industry, and most separations, that concern them by pressure swing adsorption (PSA) are carried at room temperature. By working in these conditions, we will be in the scope of application of Henry’s law, which will allow us to better characterize the adsorption of the first molecules (gas-solid interaction). The thermodynamic study should enable us to identify the type of adsorption (localized, non-localized) by applying a theoretical model explaining the experimental results. The choice of the adsorbate was guided by the behavior of the introduced molecules toward the compensating cations present in the zeolite framework. These probe molecules having a specific interaction with zeolitic cations: N2, CO2 (highly quadripolar), C2H4 (double bound) or C3H8 which do not exhibit neither. Final results show that adsorption of nitrogen on ZK-4 sodic form is made in a located way on five sites following Langmuir model and none of CO2 and C2H4 chemisorptions was revealed. Besides, the gaseous molecules interactions in presence of divalent cations replacing sodium in ZK-4 are much less higher than in the case of zeolite 4A, and are characteristic of physisorption on relatively heterogeneous sites.